EXPLORING MEDICINAL PLANT EXTRACTS AS NATURAL THERAPEUTICS FOR PEDIATRIC URINARY TRACT INFECTIONS (Journal of Medical & Health Sciences Review, 2025)
Background: Urinary tract infections (UTIs) are among the most common bacterial infections in children, and rising antimicrobial resistance has prompted interest in plant-based therapeutic alternatives.Objective: To evaluate the antimicrobial potential of selected medicinal plants against uropathogens isolated from pediatric UTI patients.Methodology: This experimental laboratory-based study was conducted at the Department of Pharmacology, University of Balochistan, Quetta, using urine samples collected from pediatric patients (aged 1–14 years) with culture-confirmed UTIs at the Sheikh Khalifa Bin Zayed Hospital, Quetta. A total of 160 non-duplicate bacterial isolates were obtained. Standard microbiological methods were used for pathogen identification, and plant extracts [Azadirachta indica (Neem), Ocimum sanctum (Tulsi), Zingiber officinale (Ginger), Nigella sativa (Black Seed)] were prepared and tested. Phytochemical screening was performed, and antimicrobial activity was assessed using agar well diffusion, MIC, and MBC assays, with comparisons made against standard antibiotics following CLSI guidelines.Results: Among 160 pediatric UTI isolates, Escherichia coli was the predominant pathogen (61.25%), followed by Klebsiella pneumoniae (17.50%) and Proteus mirabilis (8.75%). Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, and phenolics in most extracts. Ocimum sanctum (Tulsi) exhibited the highest antimicrobial activity with inhibition zones of 15.6 ± 1.4 mm against E. coli and 14.1 ± 1.3 mm against Klebsiella pneumoniae, followed by Nigella sativa (Black seed) with 14.3 ± 1.2 mm. Minimum inhibitory concentration (MIC) values for Tulsi ranged from 100–130 µg/mL, while Nigella sativa showed 150–200 µg/mL. Both extracts outperformed ampicillin (10.9–12.3 mm) but were slightly less effective than nitrofurantoin (15.6–18.5 mm) and ciprofloxacin (18.9–22.3 mm)Conclusion: Medicinal plants, particularly Tulsi and Black seed, show promising antimicrobial activity and may serve as adjunct or alternative therapies in pediatric UTI management.